On the front lines of democracy: perceptions of electoral officials and democratic elections. Issue 8 (17th November 2019) - Garnett, Holly Ann
ABSTRACT: Electoral officials play a crucial role in instilling confidence in elections and democracy. They are involved in the most important tasks of running elections, from registering voters to counting the ballots. This article employs survey data from 35 countries from the sixth wave of the World Values Survey (2010–2014) which asks respondents about their perceptions of electoral integrity and the quality of democracy in their country. The analysis demonstrates the relationship between perceptions of the fairness of electoral officials and two important outcomes: confidence in the fairness of the vote count, and perceptions of the overall quality of democracy. It additionally considers under which circumstances this relationship is most pronounced and shows that the relationship between an individual's perceptions of electoral officials and perceptions of electoral integrity is more pronounced in countries where there is a low liberal democracy index.